2012
DOI: 10.1016/j.spmi.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen photo-adsorption related quenching of photoluminescence in group-III nitride nanocolumns

Abstract: GaN and InGaN nanocolumns of various compositions are studied by room-temperature photoluminescence (PL) under different ambient conditions. GaN nanocolumns exhibit a reversible quenching upon exposure to air under constant UV excitation, following a t 1/2 time dependence and resulting in a total reduction of intensity by 85-90%, as compared to PL measured in vacuum, with no spectral change. This effect is not observed when exposing the samples to pure nitrogen. We attribute this effect to photoabsorption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
4
21
0
Order By: Relevance
“…As mentioned in Sec. III, Raman scattering shows the electron concentration in our nanowires to be below 10 17 16 , and 10 17 cm −3 (blue, green, and red solid lines, respectively). These values are reliable only above the black dashed line, which thus shows the lower limit for a given set of φ and N D for which the surface potential can be considered to be parabolic.…”
Section: Surface-induced Parabolic Potentialmentioning
confidence: 89%
See 2 more Smart Citations
“…As mentioned in Sec. III, Raman scattering shows the electron concentration in our nanowires to be below 10 17 16 , and 10 17 cm −3 (blue, green, and red solid lines, respectively). These values are reliable only above the black dashed line, which thus shows the lower limit for a given set of φ and N D for which the surface potential can be considered to be parabolic.…”
Section: Surface-induced Parabolic Potentialmentioning
confidence: 89%
“…Indirect evidence for the coexistence of neutral and ionized donors even at low temperatures has been obtained in the experiments reported in Refs. [8,17].…”
Section: Binding Energy Of Donors In the Presence Of Internal Elecmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is generally 7 accepted that adsorbed oxygen results in a decrease of the carrier lifetime that can be measured by PL. 12,13 Under illumination, we observe a variation of the NW conductivity Δσ. Keeping in mind that the conductivity is given by σ = enμ, where e is the electronic charge, n is the carrier density, and μ is the carrier mobility, a change in conductivity, Δσ = e(μΔn+nΔμ), can occur either due to change in the carrier concentration, Δn, or to a change in the carrier mobility, Δμ .…”
mentioning
confidence: 91%
“…Lefebvre et al have reported a strong influence on the PL intensity of bare GaN NWs under different atmospheres. 13 In particular, 20 The growth parameters applied for NWs on diamond are equivalent to those on Si substrate. However, GaN NW growth on diamond is characterized by a slightly thicker diameter of the NWs compared to NWs on Si due to an enhanced lateral growth (SEM images in Fig.…”
Section: Resultsmentioning
confidence: 99%